Electrical nerve stimulation to promote micturition in spinal cord injury patients: A review of current attempts. Issue 3 (8th February 2015) - Ren, Jian; Chew, Daniel J.; Biers, Suzanne; Thiruchelvam, Nikesh
Abstract : Aims: In this review, we focus on the current attempts of electrical nerve stimulation for micturition in spinal cord injury (SCI) patients. Methods: A literature search was performed through PubMed using "spinal cord injury, " "electrical nerve stimulation AND bladder, " "sacral anterior root stimulation/stimulator" and "Brindley stimulator" from January 1975 to January 2014. Results: Twenty studies were selected for this review. Conclusion: Electrical nerve stimulation is a clinical option for promoting micturition in SCI patients. Well‐designed, randomized and controlled studies are essential for further investigation. Neurourol. Urodynam. 35:365–370, 2016 . © 2015 Wiley Periodicals, Inc.